Learning Support for Students with Special Needs at a Public University from the Perspective of Non Academic Staffs - Manisah Mohd. Ali; Tarmizi Ahmad; Norshidah Mohamad Salleh; Rosadah Abd. Majid (Department of Special Education, 2018)
Learning support can be defined as support, assistance or services delivered to students with special needs to ensure that they gain full benefit from the teaching and learning process. This research was conducted to look at the learning support received by students with special needs while pursueing their study at a university. This is a case study at a public university in Malaysia. Samples were 6 non academic staffs serving various departments and units at the university. The instrument used to gather the data, was an interview protocol to survey learning support delivered by the non academic staff to students with special needs. The qualitative data was analyzed to describe forms of learning supports delivered to students with special needs. This study found that learning supports provided by the non academic staffs for students with special needs was at average level. The learning support provided include aspects on financial, motivation, career programs, special workshops and demonstrations methods, offering information package, and informing faculties as well as lecturers about the enrolment of students with special needs at the university. This study has implications on the staff professional development programme.